2004
DOI: 10.1097/01.md.0000145369.25558.b5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Traditional Risk Factors of Atherosclerosis in the Development of Severe Ischemic Complications in Giant Cell Arteritis

Abstract: Because the prognosis of giant cell arteritis (GCA) is related to the development of ischemic complications, we sought to assess the possible influence of traditional risk factors of atherosclerosis in the development of severe ischemic complications of GCA. We conducted a retrospective study of patients with biopsy-proven GCA diagnosed from 1981 to 2001 at the single hospital for a well-defined population of almost 250,000 people. Patients were considered to have severe ischemic manifestations if they suffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
4
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(105 citation statements)
references
References 14 publications
5
86
4
10
Order By: Relevance
“…Based on a series of 210 biopsy-proven GCA patients assessed for the risk of severe ischemic complications, we observed that the presence of traditional risk factors of atherosclerosis before the diagnosis of this vasculitis, in particular a history of hypertension, significantly increased the risk of developing severe ischemic complications of GCA (69). Also, patients with traditional atherosclerosis risk factors were found to have fever less commonly than those without classic atherosclerosis risk factors (69).…”
Section: Influence Of Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a series of 210 biopsy-proven GCA patients assessed for the risk of severe ischemic complications, we observed that the presence of traditional risk factors of atherosclerosis before the diagnosis of this vasculitis, in particular a history of hypertension, significantly increased the risk of developing severe ischemic complications of GCA (69). Also, patients with traditional atherosclerosis risk factors were found to have fever less commonly than those without classic atherosclerosis risk factors (69).…”
Section: Influence Of Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
“…It is possible that, due to a severe and maintained inflammatory response, fever might represent the clinical expression of an angiogenic activity, which might play a compensatory role for ischemia in patients with GCA. According to that, GCA patients with atherosclerosis would be unable to establish appropriate angiogenic compensatory mechanisms and, due to this, they might have more vascular ischemic complications (69).…”
Section: Influence Of Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
“…In patients with giant cell arteritis, 50%-75% of strokes occur in the vertebrobasilar circulation (compared with 15%-20% of strokes in patients without giant cell arteritis). 6,10 Our patient developed bilateral occlusion of the vertebral arteries, which was confirmed by cerebral angiography. This occurs in only 0.1%-0.2% of patients with cerebrovascular disease.…”
Section: Investigationsmentioning
confidence: 89%
“…Gonzalez-Gay et al (24) found that the presence of risk factors for atherosclerosis at the time of GCA diagnosis significantly increased the risk of developing at least one of the severe ischemic complications of the disease. Two case-control studies have shown an increased risk of GCA in heavy smokers and in patients with previous atherosclerotic disease (cardiovascular or peripheral vascular disease) (25,26).…”
Section: Discussionmentioning
confidence: 99%